Bone, microbiological and intestinal characteristics of piglets fed diets containing Lithothamnium calcareum - Genova, J. L.; Oliveira, N. T.E.; Scherer, C. P.; Carvalho, P. L.O.; Costa, A. B.S.; Artoni, S. M.B. [UNESP]; Júnior, A. C.G.; Santos, L. B.A.; Carvalho, S. T.; Bortoluzzi, J. (Academy of Science of South Africa, 2022)
The aim of this study was to assess the effect of calcitic seaweed (CS), calcitic limestone (CL) and monodicalcium phosphate (DP) fed to piglets in various combinations on their gastrointestinal tract and bones. A total of 128 piglets (21 days old, 5.50 ± 0.49 kg bodyweight (BW) were assigned to treatments in a randomized complete block design and eight replications to one of four diets: D1: with CL + DP, D2: with CL, CS + DP, D3, similar to D2, but with 30% less calcium from CS and DP, and D4: with CS + DP. Treatments affected the metatarsal bones, mineral concentration in the heart and liver, and pH in the cecum and colon. Piglets fed D4 tended to have a greater Enterobacteriaceae count in the jejunum and ileum compared with D1 (4.82 vs 4.79 CFU/g). Piglets fed D1 and D3 had a greater Enterobacteriaceae count in their cecum than D4 (4.79 and 4.80 vs 4.76). The D2 and D1 treatments produced greater crypt depth (CD) in the duodenum and ileum compared with D3 and D4, respectively. Feeding D3 resulted in a greater villus height (VH) to CD ratio in the duodenum compared with D2 and showed a 24.5% increase in heart weight compared with fed D1. In conclusion, CS could be an alternative source of calcium source for piglets. The inconsistent findings of the present study suggest the need for further studies to better understand the interplay of effects of Ca2+ source and level on its metabolism. ______________________________________________________________________________________.
Keywords: bone density; calcitic limestone; intestinal microbiota; seaweed; weanling swine